TPM Implementation in Ceramic Tile Industry - Cecep Hermawan; Hasbullah Hasbullah (Journal of Industrial Engineering & Management Research, 2023)
To increase industrial growth in Indonesia, especially the ceramic tile industry, it must increase productivity on production floors. The purpose of this study is, firstly, to find out the causes of the Overall Equipment Effectiveness (OEE) level in a company that does not meet the expected standards. Second, to determine what improvements should be made to increase the OEE on the packing machine. This research uses a case study in a tile manufacturing industry located in Cikarang, Indonesia. The focus of this research is on packing machines using pneumatic and electric systems. The analysis was carried out by applying Failure Mode and Effect Analysis (FMEA) with the support of other tools such as Cause and Effect Diagrams (CED), and 6 big losses analysis. By adhering to the entire research framework, find the reasons why OEE does not meet the target. From these results, it can be concluded that the application of these methods has a positive impact on the company. The OEE rate increased from an average of 72.5% to 94.5%. It means the OEE level has reached the standard of world-class manufacturing.